CFD Simulation of Biomass Pyrolysis in a Fluidized Bed Reactor: Effect of Particle Shrinkage Model - Thoharudin, Thoharudin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study implemented the improved multistep comprehensive reaction for pyrolysis in a fluidized bed reactor. Particle shrinkage models were developed with variations of constant and nonconstant particle size with different char densities. Different biomass particle sizes were also investigated to observe their decomposition characteristic in a fluidized bed reactor. A multifluid model framework integrated with heterogeneous chemical reactions was developed to simulate fast biomass pyrolysis in a 2-D computational domain. The improved multistep comprehensive reaction exhibited good agreement with experimental pyrolysis product yields and their compositions. Shrinkage models with constant particle size promoted segregation and tended to generate coarse gradients between the dense zone and the freeboard. By contrast, the shrinkage models with nonconstant particle size favored more homogeneous biomass and char & metaplastic mass fractions in the reactor and reduced segregation. Models 4–6 exhibited positive representations of particle shrinkage with particle volume reductions of 54.4%, 54.3% and 50.7%, respectively